Efek Pemberian Ekstrak Etanol Daun Alpukat (Persea Americana Mill) Terhadap Penyembuhan Luka Bakar Pada Kelinci (Oryctolagus Cunicullus) - Wahyu Tri Pamungkas; Siwi Hastuti; Sri Saptuti Wahyuningsih (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Burns are injuries caused by direct body contact with hot objects or exposed to fire. Burns not only cause skin damage, but can also affect the body's systems. Avocado leaf (Persea americana Mill) is a medicinal plant known to contain compounds that play a role in wound healing, such as flavonoids, saponins, tannins and alkaloids. This study aims to determine the ethanol extract of avocado leaves has an effect on healing burns in rabbits. Avocado leaf extract was prepared by maceration using 70% ethanol as a solvent. The wound healing test in rabbits were divided into 5 treatment groups, namely the positive control group which was given lavertan ointment, the negative control group was given yellow vaseline, and 3 test groups were given ethanol extract of avocado leaves with a concentration of 5%, 10% and 20%. Making burns using a heated iron plate was then given to the rabbit's back for 5 treatments. Rabbits were observed every day for one week with statistical analysis One Way ANOVA test. The ethanol extract of avocado leaves with a concentration of 5% 10% and 20% had the effect of wound healing 5% = (11, 27 ± 0.16)%, 10% = (12.62 ± 0.14)%, and 20% = (19.86 ± 0.14)%, which means that the ethanol extract of avocado leaves has positive results on wound healing in rabbits. Avocado leaf ethanol extract can be used to heal burns in rabbits.